ON FIMDAMENTAL PRINCIPLE OF THE ALLOYS MODIFICATION THEORY - V. Yu. Stetsenko (Литьë и металлургия)
It is shown that the basis of the theory of alloys modification is refinement of nano-crystals surfaces and growing crystallizing centers of the phases from blocking surface-active elements and molecular hydrogen.